Johnson and Boswell a biography of friendship - Radner, John B. (Yale University Press, 2012)
In this book John Radner examines the fluctuating, close, and complex friendship enjoyed by Samuel Johnson and James Boswell, from the day they met in 1763 to the day when Boswell published his monumental Life of Johnson. Drawing on everything Johnson and Boswell wrote to and about the other, this book charts the psychological currents that flowed between them as they scripted and directed their time together, questioned and advised, confided and held back. It explores the key longings and shifting tensions that distinguished this from each man's other long-term friendships, while it tracks in detail how Johnson and Boswell brought each other to life, challenged and confirmed each other, and used their deepening friendship to define and assess themselves. It tells a story that reaches through its specificity into the dynamics of most sustained friendships, with their breaks and reconnections, their silences and fresh intimacies, their continuities and transformations.